2020
DOI: 10.5194/tc-14-3155-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating permafrost physics in the Coupled Model Intercomparison Project 6 (CMIP6) models and their sensitivity to climate change

Abstract: Abstract. Permafrost is a ubiquitous phenomenon in the Arctic. Its future evolution is likely to control changes in northern high-latitude hydrology and biogeochemistry. Here we evaluate the permafrost dynamics in the global models participating in the Coupled Model Intercomparison Project (present generation – CMIP6; previous generation – CMIP5) along with the sensitivity of permafrost to climate change. Whilst the northern high-latitude air temperatures are relatively well simulated by the climate models, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 62 publications
4
107
0
Order By: Relevance
“…CMIP5 results showed a projected areal loss of permafrost in the northern regions of between 30% to 90%, with most of the loss occurring by the end of the 21 st century (McGuireet al, 2018). Similarly, Burke et al (2020) reported projected permafrost degradation of the upper 2m of soil of 10% -40% per 1.0°C increase in global mean air temperature from the CMIP6 multi-model ensemble. Notably, permafrost contains twice the amount of carbon stored in the atmosphere, the release of which would accelerate the pace of global warming via a positive feedback mechanism (Schuuret al , 2015;Walvoord and Kurylyk, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…CMIP5 results showed a projected areal loss of permafrost in the northern regions of between 30% to 90%, with most of the loss occurring by the end of the 21 st century (McGuireet al, 2018). Similarly, Burke et al (2020) reported projected permafrost degradation of the upper 2m of soil of 10% -40% per 1.0°C increase in global mean air temperature from the CMIP6 multi-model ensemble. Notably, permafrost contains twice the amount of carbon stored in the atmosphere, the release of which would accelerate the pace of global warming via a positive feedback mechanism (Schuuret al , 2015;Walvoord and Kurylyk, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…The presence of permafrost in high-latitude landscapes crucially affects hydrological and biogeochemical processes and makes their realistic representation within macro-scale LSM frameworks challenging (Chadburn et al, 2017;Andresen et al, 2020;Burke et al, 2020). Beyond the requirement to accurately simulate freeze-thaw processes near the surface, the presence of excess ice in the subsurface is an additional source of complexity.…”
Section: Implications For Simulating High-latitude Land Surface Procementioning
confidence: 99%
“…9 ). Burke et al ( 2020 ) reported that permafrost sensitivity—the change in permafrost volume per degree of global mean surface air temperature change—is 20–30% using CMIP5/CMIP6 data. Although these authors analyzed the uncertainty ranges in multi-model ensembles of CMIPs, the present study could examine the response of a global land surface model by considering the uncertainty in atmospheric model projection.…”
Section: Future Simulationsmentioning
confidence: 99%